A retrospective analysis of two tertiary care dizziness clinics: a multidisciplinary chronic dizziness clinic and an acute dizziness clinic - Phillip Staibano; Daniel Lelli; Darren Tse (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Vertigo remains a diagnostic challenge for primary care, emergency, and specialist physicians. Multidisciplinary clinics are increasingly being employed to diagnose and manage patients with dizziness. We describe, for the first time in Canada, the clinical characteristics of patients presenting with chronic and acute dizziness to both a multidisciplinary chronic dizziness clinic (MDC) and a rapid access dizziness (RAD) clinic at The Ottawa Hospital (TOH). Methods We performed a retrospective review of all patients presenting to the MDC and RAD clinics at TOH from July 2015 to August 2017. Results Overall, 211 patients (median age: 61 years old) presented to the RAD clinic and 292 patients (median age: 55 years old) presented to the MDC. In the RAD clinic, 63% of patients had peripheral dizziness, of which 55% had BPPV, and only one patient had functional dizziness. Interestingly, only 25% of RAD diagnoses were concordant with emergency department diagnoses; moreover, only 33% of RAD patients had HiNTS completed, while 44% had CT scans, of which only one scan had an abnormal finding. Prior to assessment, all patients in the MDC had an unclear cause of dizziness. 28% of patients had vestibular dizziness and 21% had functional dizziness, of which 43% had persistent postural perceptual dizziness. Moreover, 12% of patients with functional dizziness also suffered from comorbid severe anxiety and depression. Conclusions Dizziness is a heterogeneous disorder that necessitates multidisciplinary care, and clinics targeting both the acute and chronic setting can improve diagnostic accuracy, ensure appropriate diagnostic testing, and facilitate effective care plans for patients with dizziness.